The Impact Of Rural Tourist Recreational Space Design On Tourism Development And Tourist Attraction In Iran - Yousefi, Kianoosh (The Turkish Online Journal of Design Art and Communication, 2016)
Rural development and thus, country development is a multi-dimensional process which its subject is improving the quality of life of the vulnerable villagers. One of the development dimensions which can have the overall impact on people's lives is the expansion of tourism. Rural tourism is considered as a process in rural development which can evolve village economy and environment by creating complementary activities and thus, leads to improve the quality of life and a balanced and proportional distribution of services and facilities. If rural tourism be done planned and purposeful, it can be protected from injuries which tourist causes. One way of making this process purposeful is creating specific spaces with capability of transform into recreational spaces. Centralizing tourist recreational services providing with the goal of creating an appropriate service atmosphere causes maintaining order and control of the environment and creating ecological balance. In this article, we are going to learn about importance of designing these spaces in villages and its role in the development of the national tourism industry.
Keywords: tourism development; rural tourist recreational spaces; rural development; tourism